Environmental taxation and the law - Milne, Janet E., 1951- (International library of law and the environment, 2017)
Economics shapes environmental pricing theory, but the law translates theory into reality. This research review examines and discusses carefully selected classic and cutting edge articles from around the world that delve into the legal design features of environmental tax instruments, how governments define the legal authority to use environmental taxation, complex interactions with WTO law and the legal conundrums of border tax adjustments. These influential articles cover a wide range of environmental and legal issues that recur across continents, with carbon taxes and climate change taking centre stage as important case studies. This timely review is an essential resource for those working in the field, whether they are trained in law, economics, political science, environmental science or public finance.